2017
DOI: 10.3390/molecules22122233
|View full text |Cite
|
Sign up to set email alerts
|

HIGA: A Running History Information Guided Genetic Algorithm for Protein–Ligand Docking

Abstract: Protein-ligand docking is an essential part of computer-aided drug design, and it identifies the binding patterns of proteins and ligands by computer simulation. Though Lamarckian genetic algorithm (LGA) has demonstrated excellent performance in terms of protein-ligand docking problems, it can not memorize the history information that it has accessed, rendering it effort-consuming to discover some promising solutions. This article illustrates a novel optimization algorithm (HIGA), which is based on LGA for sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…For each tested algorithm, the number of iterations was 27,000 and the number of individuals was 100. The other parameters were set in accordance with previous studies [31,32,33,34,35], and the details are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each tested algorithm, the number of iterations was 27,000 and the number of individuals was 100. The other parameters were set in accordance with previous studies [31,32,33,34,35], and the details are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The ideal search algorithm should be able to enumerate all possible binding poses between ligands and receptors, but this is difficult to achieve because the search space involved in molecular docking is huge. Many evolutionary computation methods have been presented for solving protein–ligand docking problems [22,23,24,25,26,27,28]: for example, simulated annealing (SA) [29], genetic algorithm (GA) [30], Lamarckian genetic algorithm (LGA) [31], running history information guided genetic algorithm (HIGA) [32], and swarm optimization for highly flexible protein–ligand docking (SODOCK) [33]. These methods have been applied to solve docking problems, but they have some drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…24 Prochek Ramachandran plot was used for the validation of target protein (2i54) defined by the phi (j) and psi (y) angles, the number of amino acid residues shown in the most favorable region is 90.8%, the additional allowed region is 8.9%, generously allowed regions are 0.3% and the Lamarckian Genetic Algorithm. 30 After each protein-ligand complex interactions, among the 9 poses, the best pose based on its conformation and binding affinity was selected, and obtained RMSD (Root Mean Square Deviation) values. 31 The RMSD values (UB/LB) zero refers to good interaction between protein and ligand.…”
Section: Target Preparation and Validationmentioning
confidence: 99%
“…PyRx 0.8, along with AutoDock Vina v.1.1 28 , was used for structure-based docking studies of Mpro with FDA approved ligand molecules. The software was selected owing to its rapid yet efficient search capability to find accurate and active conformations 29 . While the SARS-CoV2 Mpro protein molecule was considered as a rigid structure, ligand drug molecules were considered flexible during the docking process.…”
Section: -Structure-based Virtual Screeningmentioning
confidence: 99%